Geochemistry of Fluid Inclusions in Travertines From Western and Northern Turkey: Inferences on the Role of Active Faults in Fluids Circulation. (30th November 2019) - Rizzo, Andrea Luca; Uysal, I. Tonguc; Mutlu, Halim; Ünal‐İmer, Ezgi and Dirik, Kadir and Yüce, Galip and Caracausi, Antonio and Italiano, Francesco and Misseri, Mariagrazia and Temel, Abidin and Bayarı, Serdar and Özyurt, Nur and Zhao, Jian‐xin and Deniz, Kıymet
Abstract: The understanding of the relationship between the geochemistry of fluids circulating during travertine deposition and the presence of active faults is crucial for evaluating the seismogenetic potential of an area. Here we investigate travertines from Pamukkale and Reşadiye (Turkey), sited in seismic regions and next to thermal springs. These travertines formed 24, 500–50, 000 (Pamukkale) and 240–14, 600 years (Reşadiye) BP. We characterize fluid inclusions (FIs) and studied concentration of H2 O, CO2, O2 + N2, and 3 He, 4 He, 20 Ne, and 40 Ar, and bulk composition (trace elements and δ 13 C‐δ 18 O). FIs from both localities are mainly primary with low salinity and homogenization temperature around 136–140 °C. H2 O is the major component followed by CO2, with the highest gas content measured in Pamukkale travertines. Concentrations of Ne‐Ar together with O2 + N2 indicate that travertines from both areas precipitated from atmosphere‐derived fluids. The 3 He/ 4 He is 0.5–1.3 Ra in Pamukkale and 0.9–4.4 Ra in Reşadiye. Samples with R/Ra > 1 are modified by cosmogenic 3 He addition during exposure to cosmic rays. Excluding these data, FIs of Reşadiye are mostly atmosphere‐derived. This implies a shallow formation where the circulation was dominated by meteoric waters, which is consistent with their young age. Instead, FIs of Pamukkale show mixing of mantle‐, crustal‐, and atmosphere‐derived He, indicating that these travertines formed in lithospheric fractures. Based on the δ 13 CCO2 and δ 18 O of bulk rocks, we infer that travertines formed involving crustal‐ (mechanochemical rather than organic) and mantle‐derived CO2 . Trace elements of Pamukkale and Reşadiye show comparable rare earth element patterns. We conclude that travertines formed in response of seismogenetic activity. Key Points: We studied the geochemistry of fluid inclusions in travertine deposits from Pamukkale and Reşadiye areas (Turkey). Concentrations of Ne‐Ar and O2 +N2 indicate that travertines from both areas precipitated from atmosphere‐derived fluids. The 3 He/ 4 He values indicate that Reşadiye travertines formed at shallow depth, while Pamukkale in an active system of lithospheric fractures